Destiny : Der müde Tod [videorecording (DVD)] - Lang, Fritz, 1890-1976; Harbou, Thea von, 1888-1954; Goetzke, Bernhard, 1884-1964; Dagover, Lil; Janssen, Walter, 1887-1976; Sternberg, Hans, 1878-1948; Diegelmann, Wilhelm, 1861-1934; Klein-Rogge, Rudolf; Nitzschmann, Erich, 1901-1980; Saalfrank, Herrmann; Wagner, Fritz Arno, 1894-1958; Schwehr, Cornelius (Kino Classics, 2016)
A young woman confronts the personification of Death, in an effort to restore life to her dead fiancé.